Examining The Impact of E-Service Quality and E-Recovery Service Quality in Digital Public Services in Indonesia - Yovian Yovian; Novandra Rhezza Pratama (Journal of World Science, 2025)
Digital government services are increasingly delivered through applications that interact directly with users and offer the potential to enhance public service efficiency. This study investigates the impact of e-service quality and e-recovery service quality on customer experience, satisfaction, and loyalty within the context of digital public services. Constructs such as efficiency, fulfilment, security, and availability represent e-service quality, while compensation, responsiveness, and contact reflect e-recovery service quality. The relationships between these constructs and the dimensions of customer experience, satisfaction, and loyalty were examined using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through a questionnaire distributed to users of digital services at the Legal Metrology Standardization Regional IV Office, Ministry of Trade of the Republic of Indonesia. A total of 273 valid responses were analyzed from customers who had used the digital service within the past year. The findings reveal that both e-service quality and e-recovery service quality significantly influence customer experience, satisfaction, and loyalty. This study offers new insights into how customer loyalty is shaped in the context of government-provided digital services.